Polymer electrolytes based on poly(metyhyl methacrylate) (PMMA) : characterization for application in lithium polymer battery / Ab Malik Marwan Ali - Ali, Ab Malik Marwan (2008)
In the present study, poly(meythyl methacrylate) (PMMA), 30% PMMA-graftednatural rubber (MG3 0), lithium triflouromethanesulfonate (LiCF 3 SO3 or LiTf),propylene carbonate (PC) and ethylene carbonate (EC) were used in the preparation of solid polymer electrolytes (SPE) and gel polymer electrolytes (GPE). All samples it were prepared by solution cast technique. SPE and GPE were characterized by means of physical and electrical spectroscopy in order to find the suitable polymer electrolytes composition for fabrication in lithium polymer cell. The conductivity of all samples was calculated using the bulk resistance value obtained from the complex impedance plot in the frequency range 100 Hz to 1 MHz. The SPE film containing 35 wt.% LiTf in PMMA:LiTf and MG30:LiTf exhibit the highest conductivity of 5.80 x 10 S cm-1 and 8.39 x 10 S cm, respectively, at room temperature.